2013
DOI: 10.1016/j.jvs.2013.02.248
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of pararenal aortic aneurysms with multiple overlapping uncovered stents

Abstract: An alternative method of management of complicated aortic aneurysm appears to be feasible using overlapping bare stents, which may prevent aneurysm growth while preserving vital branches. The short-term outcome of our study seems encouraging but is not sufficient to draw a robust conclusion. Further hemodynamic and clinical studies are warranted to evaluate long-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…A larger D/N ratio could lead to a more significant decrease in wall shear stress within the aneurysm sac. This theory is in accordance with our previous clinical investigation [13], in which we found that the aneurysm SE length could influence the thrombosis process within the sac. While the dome length is fixed for a given aneurysm, the neck length could be shortened by a stent graft covering part of it.…”
Section: Commentsupporting
confidence: 93%
See 3 more Smart Citations
“…A larger D/N ratio could lead to a more significant decrease in wall shear stress within the aneurysm sac. This theory is in accordance with our previous clinical investigation [13], in which we found that the aneurysm SE length could influence the thrombosis process within the sac. While the dome length is fixed for a given aneurysm, the neck length could be shortened by a stent graft covering part of it.…”
Section: Commentsupporting
confidence: 93%
“…For a TAAA that mainly affected the infrarenal aorta rather than the thoracic aorta (type Ⅳ TAAA), a "reversed procedure" could be considered, in which the stent graft (Hercules-B, MicroPort) could be placed at the infrarenal aorta to cover the distal aneurysm SE, while the multiple bare stents were deployed above it to cover the proximal aneurysm residual SE (Fig 3B). The aneurysm sac entrance was defined as the threshold between the normal laminar flow of the native aorta and the turbulent flow of aneurysm sac (A: sac entrance for saccular aneurysms; B: sac entrance for fusiform aneurysms), whose length could exert an influence on the thrombosis process of the aneurysm sac according to our previous study [13]. The length of the aneurysm sac entrance could be artificially shortened by a stent graft covering part of it.…”
Section: Procedural Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation also supports clinical studies that use three to four MOUS stents and reported encouraging short-term outcomes (25). In the clinical setting, the number of uncovered stents implanted can be determined by intraoperative angiography with the criterion of velocity reduction in aneurysm sac achieved on fluoroscopy (22,23,26). To avoid perfect overlapping of stents, the alignment of stent can be adjusted circumferentially during deployment by referring to the radiopaque markers located at both proximal and distal end of the stent.…”
Section: Discussionsupporting
confidence: 65%